Investigating the Association between rs17859812 Polymorphism in MUC5AC Gene Promoter and Risk of Gastric Cancer - Mehdi Moghanibashi (Fasa University of Medical Sciences, 2017)
Background & Objective: MU5AC gene plays a key role in the maintenance of gastric mucosa against harmful factors in the stomach through encoding a main mucin of mucus lining gastric mucosa and its expression is reduced in the gastric cancer. In this study, due to the effect of genetic polymorphisms in the promoter region on the gene expression, the association between single nucleotide polymorphism of MU5AC gene promoter and the risk of gastric cancer was assessed. Materials & Methods: in this case-control study, a fragment of MUC5AC gene promoter was amplified by PCR technique in 50 individuals and rs17859812 single nucleotide polymorphism was selected by sequencing, and other subjects were genotyped using PCR-RFLP method. Finally, logistic regression and chi-square tests were used for data analysis. Results: Following sequencing and PCR-RFLP, the findings showed that allele C in the -221 of the promoter increased the risk of gastric cancer (OR= 1.66, CI= 3.09-5.18, p = 0.008) and CC genotype increased the risk of gastric cancer (OR= 4.66, CI= 2.09-10.38, p< 0.001). Also, CC + CT genotypes increased the risk of gastric cancer (OR=2.08, CI= 3.1-7.45 p= 0.007). Conclusion: The results of this study showed that allele C in the rs17859812 polymorphism of the MUC5AC gene is associated with the risk of gastric cancer. As this polymorphism is located in the vicinity of the glucocorticoid receptor binding site, it may affect the MUC5AC gene expression and may result in gastric cancer susceptibility.